Komunikasi Dakwah Ulama Sumatera Selatan - Nurseri Hasnah Nasution (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2018)
South Sumatra cleric is the heir of a prophet who has a charismatic authority. They have insights and views that are not limited by space and time (yatafaqquh al-din). Commited, they communicate verbal and non verbal dakwah. They have the quality of cendicia behavior. The Qur'an calls it the term ulul albab. This Qur'anic terminology indicates that South Sumatran clerics are capable of transforming Islamic values into the souls of communicans (the people of South Sumatra). In addition, the scholars' ability in communicating da'wah also indicates that they are Muslim scholars who possess wisdom (al-hikmah, wisdom) which produce abundant virtues (khair katsiran). They responded to various problems of the people of South Sumatra through the communication of da'wah. One of the South Sumatra clerics who actively communicates da'wah is K.H. Muhammad Zen Shukri. He conducts verbal and non verbal dakwah communication so that some problems of the people of South Sumatra can be overcome. He is active in lectures, establishing educational institutions, writing books, establishing places of worship, establishing Islamic institutions, political movements, giving uswah.